The effect of building-level socioeconomic status on bystander cardiopulmonary resuscitation: a retrospective cohort study. (3rd October 2022) - Ho, J; Ho, A F W; Ting, P Z Y; Fook-Chong, S F; Ahmad, N S; Pek, P P; Liu, N; Teoh, S; Sia, C H; Lim, D Y Z; Lim, S L; Wong, T H; et al.
Abstract: Background/Introduction: In out-of-hospital cardiac arrest (OHCA), bystander cardiopulmonary resuscitation (BCPR) increases survival [1]. Understanding the social determinants of BCPR receipt can inform the design of public health interventions to increase BCPR. The association of socioeconomic status (SES) with BCPR is generally poorly understood. Purpose: We aimed to evaluate the effect of SES on BCPR in OHCA using a building-level SES marker. Methods: This was a retrospective cohort study based on the Singapore cohort of the Pan-Asian Resuscitation Outcomes Study registry, an ongoing long-term prospective registry for OHCA in the Asia-Pacific region, between 2010 to 2018. We categorized patients into low, medium and high Singapore Housing Index (SHI) levels. The SHI, which appraises a residential property value on an ordinal scale of 1 to 7 (low to high), is a building-level marker that has a robust association with income and residence value [2]. The primary outcome was receipt of BCPR. The secondary outcomes were pre-hospital return of spontaneous circulation (ROSC) and survival – defined as survival to 30 days or hospital discharge, whichever occurred first. Results: A total of 12, 730 OHCA cases were included (Figure 1), the median age was 71 years and 58.9% were male. BCPR rate was 56.7%. OHCA patients in the low SHI tier were the youngest, most likely male, and least likely to have any medical co-morbidities (Table 1). Compared the low SHI category, those in the medium and high SHI categories were more likely to receive BCPR (medium SHI: adjusted odds ratio [aOR] 1.483, 95% CI 1.301–1.691, p<0.01; high SHI: aOR 1.933, 95% CI 1.669–2.240, p<0.01). As a continuous variable, every unit increase in SHI was associated with increased BCPR (aOR 1.142, 95% CI 1.110–1.174, p<0.001). High SHI patients had higher survival compared to low SHI patients on unadjusted analysis (OR 1.789, 95% CI 1.080–2.964) but not adjusted analysis (adjusted for age, sex, race, witness status, arrest time, past medical history of cancer, and first arrest rhythm). There were no significant differences in the proportion of ROSC across three categories of SHI (p=0.426). When comparing high with low SHI, females had larger increases in BCPR rates compared to males (ratio of OR 1.370, 95% CI 1.012–1.853). There were no significant associations between SHI and BCPR in the subgroups age ≥65 years, witnessed arrest, daytime arrest, and arrests after 2014, and no interaction effects were observed. Conclusions: Lower building-level SES was independently associated with lower rate of BCPR. Higher SES was associated with higher 30-day survival on unadjusted analysis but not adjusted analysis, and this study may be under-powered for this outcome. Females were more susceptible to the effect of low SES on lower rate of BCPR, and community CPR training should focus on recognizing OHCA and performing BCPR in women in low SES communities. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Medical Research Council, Clinician Scientist Awards, Singapore (NMRC/CSA/024/2010, NMRC/CSA/0049/2013 and NMRC/CSA-SI/0014/2017) and Ministry of Health, Health Services Research Grant, Singapore (HSRG/0021/2012).